Pertussis and Bronchopneumonia in a One-Month-Old Infant: A Case Report: Pertussis and Bronchopneumonia in a One-Month-Old Infant: A Case Report - Virgiansya Alhafiz; Shinta Nareswari (Medula, 2026)
Pertussis and bronchopneumonia are significant respiratory tract infections that cause high morbidity and mortality in young infants. The combination of these two conditions poses a severe clinical challenge, particularly in patients with an immature immune system who have not yet received immunization. This case report aims to discuss the diagnostic challenges regarding the CDC/WHO criteria for probable pertussis, the importance of intensive monitoring parameters, and the simultaneous management of atypical manifestations in young infants. A 1-month-11-day-old male infant presented with an 8-day history of paroxysmal cough, accompanied by post-tussive cyanosis, dyspnea, and nocturnal fever, with episodes of apnea. The patient had not received the DPT vaccination. Household contact tracing revealed that the patient's father had a history of chronic cough for the past 2 weeks and had not undergone any examination. Physical examination showed an oxygen saturation of 90% on room air and bilateral rhonchi. Laboratory evaluation revealed leukocytosis (14,900/mm³) with predominant relative lymphocytosis (68%) and thrombocytosis (561,000/μL). A chest X-ray demonstrated bilateral perihilar and right paracardiac infiltrates, confirming bronchopneumonia. Based on these findings, the patient was diagnosed with probable pertussis and bronchopneumonia. Therapeutic interventions included intravenous ampicillin-sulbactam, intravenous gentamicin, oral azithromycin, nebulized salbutamol + ipratropium bromide, and oxygen supplementation. The patient showed significant clinical recovery and was discharged on the fourth day of hospitalization. High clinical vigilance for pertussis and bronchopneumonia is vital when evaluating young infants presenting with paroxysmal cough, cyanosis, incomplete immunization status, and a history of close contact with an individual suffering from a chronic cough. The simultaneous administration of empirical macrolides and broad-spectrum antibiotics is effective in ensuring a successful clinical outcome.